DIPG-18. IDENTIFICATION OF TARGETABLE PATHWAY DEPENDENCIES IN DIFFUSE INTRINSIC PONTINE GLIOMA. (4th December 2020) - Parackal, Sarah; Chong, Wai Chin; Bradshaw, Gabrielle; Sun, Claire; Daniel, Paul; Roussel, Enola; Jayasekara, Samantha; Crombie, Duncan; Firestein, Ron; Cain, Jason
Abstract: Diffuse Intrinsic Pontine Glioma (DIPG) is a highly aggressive paediatric brainstem tumour with a dismal prognosis. Recurrent heterozygous mutations (p.K27M) in Histone H3 variant genes have been identified in the majority of DIPG cases. While the exact mechanism of H3K27M's function is poorly understood, evidence suggests a role for epigenetic dysregulation in disease pathogenesis. This study aims to use functional genomics to identify novel therapeutic dependencies in H3K27M DIPG. DIPG drug sensitivity screening was carried out in twelve established and validated patient derived cell lines (10 H3.3K27M and 2 Wt) using an FDA approved drug library containing 1480 compounds. Highly prevalent targets identified from this screen include HDAC, microtubule, proteasome and CDK inhibitors. Additionally, a custom pooled CRISPR knockout library of druggable targets (300 genes, 1200 guide RNAs) was used to identify key DIPG cell survival pathways. To date five DIPG cell lines (1 Wt; 1 H3.1; 3 H3.3) have undergone screening. Knockdown of known DIPG driver genes ( TP53; PDGFRA ; PIK3CA and PIK3CR1 ) resulted in reduced cell viability, consistent with their proposed function and validating knockout screen utility. Preliminary data demonstrates Wt and H3K27M DIPGs cluster independently based on genes required for survival, suggesting differing tumorigenesis mechanisms and the potential for therapeutically targeting genotype specific pathways. Correlation of parallel drug screen and RNA-seq data will potentially reveal H3-dependent pathways for therapeutic exploitation. Collectively, we show a functional genomics approach is able to identify genotype-specific pathway dependencies in DIPG, paving the way for molecularly informed personalized therapies for patients.